Made in Germany : studies in popular music - Seibt, Oliver HerausgeberIn; Ringsmut, Martin HerausgeberIn; Wickström, David-Emil 1978- HerausgeberIn (Routledge global popular music series, 2021)
Introduction. Deutschland - Echt jetzt? German Popular Music's Complicated Relationship with German Identity / Oliver Seibt, Martin Ringsmut, and David-Emil Wickström ; Interview : Rocking the Academy? Two Cold-War Careers and the Emergence of Popular Music Studies and Higher Popular Music Education in Germany / An Interview with Peter Wicke and Udo Dahmen / David-Emil Wickström -- Historical Spotlights. Transnational Networks and Intermedial Interfaces in German Popular Music, 1900-1939 / Caroline Stahrenberg ; Nazis and Quiet Sounds : Popular Music, Simulated Normality, and Cultural Niches in the Terror Regime, 1933-45 / Jens Gerrit Papenburg ; Conflicting Identities : The Meaning and Significance of Popular Music in the GDR / Michael Rauhut ; 'Party on the Death Strip' - Reflections on an Historical Turning Point ; Susanne Binas-Preisendörfer -- Globally German. The Krauts Are Coming : Electronic Music and Rock in the 1970s / Ulrich Adelt ; German Metal Attack : Power Metal in and from Germany / Jan-Peter Herbst ; German Longings : A Dialogue on the Promises and Dangers of National Stereotypes / Melanie Schiller and Jeroen de Kloet -- Also "Made in Germany". Peepl rock : Post-Soviet Popular Music in Germany / David-Emil Wickström ; Made in Almanya : The Birth of Turkish Rap / Thomas Solomon ; G.I. Blues and German Schlager : The Politics of Popular Music in Germany during the Cold War / Bodo Mrozek ; Explicitly German. Neue Deutsche Welle : Tactical Affirmation as a Strategy of Subversion / Barbara Hornberger ; "One Day You Will Wish We'd Only Played Music" : Some Remarks on Recent Developments of Germany's RechtsRock Scene / Thorsten Hindrichs ; Hallo Blumenau , bom dia Brasil! German Music Beyond Germany / Julio Mendívil -- Reluctantly German. "Meine Lieder sind anders" : Hildegard Knef and the Idea(l) of German Chanson / René Michaelsen ; How Munich and Frankfurt Brought (Electronic) Dance Music to the Top of the International Charts with Eurodisco and Eurodance - and Why Germany Was Not Involved / Heiko Wandler ; Japonisme 2.0 : German visual-kei Fans, Tokio Hotel, and the Popular Music Genre That Must Not Exist / Oliver Seibt -- Coda. The Germaican Connection - German Reggae Abroad / Martin Ringsmut ; Interview : Standing Up Against Discrimination and Exclusion : An Interview with Kutlu Yurtseven (Microphone Mafia) / Monika E. Schoop.